Evaluation of the effect of yellow laser (DPSS) light on human lymphocytes viability in vitro - Fatimah Saed Awad; Saba Fawzi Salih; Mustafa Salih Al Musawi (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the lymphocyte apoptotic impact of yellow laser light in vitro. Method: The experimental study was conducted from November 2021 to April 2022 at the Postgraduate Medical Physics Laboratory, Mustansiriyah University, Baghdad, Iraq, and comprised blood samples from healthy volunteers. The samples were subjected to 1:1 dilution in isotonic phosphate buffered saline, and each sample was divided into two equal aliquots; one for irradiation, and other as control.The percentage of apoptotic lymphocyte was estimated before and after radiation exposure with low-level laser 589nm at 30J/cm², 50J/cm² and 70J/cm²energy intensities. Post-exposure evaluation was done immediately, and 1 and 2 hours after radiation on theviability of normal human cells. The vitality of the cells was determined using the trypan blue exclusion test. Datawas analysed using SPSS 24. Results: There were 26 healthy volunteers (16 male, 10 females) with an age range of (20-40) years. After the exposure, the percentage of lymphocytes that apoptose increased significantly when cells were irradiated at70J/cm2 immediately compared to the controls (p less than or equal to 0.05), but there was no significant differences with the 30J/cm²dose. After 1 and 2 hours, a significant reduction in the proportion of apoptotic lymphocytes was observed (p<0.05).Conclusion: Yellow low-level laser showed a noticeable protective effect on lymphocytes by decreasing thepercentage of dead cells.Key Words: Trypan, Lymphocytes, Lasers, Radiation Exposure, Phosphates